Job Satisfaction and Turnover Intention: The Mediating Effect of Affective Commitment - Kartika, Galih; Purba, Debora Eflina (Psychological Research on Urban Society, 2018)
This study examined the mediating effects of affective commitment on the relationship between job satisfaction and turnover intention in international school teachers. Previous research that assumed the total organizational commitment score to be the mediator between job satisfaction and turnover intention, found that organizational commitment only partially mediated the relationship. Therefore, the present study contributes to the literature by focusing only the mediating effect of affective commitment as this variable has been identified as having the greatest effect on organizational outcomes compared to normative and continuance commitments. A survey was conducted on 80 teachers in an international school in Jakarta, Indonesia, the data analyzes from which found that affective commitment fully mediated the relationship between job satisfaction and turnover intention. Theoretical and practical implications are also given.